DISH in an individual from the Portuguese Navy (18th-19th centuries) - Antunes-Ferreira, Nathalie (2017)
Poster apresentado nas V Jornadas Portuguesas de Paleopatologia, 25-26 Novembro 2016. Coimbra, Portugal